Working alliance in low-intensity internet-based cognitive behavioral therapy for depression in primary care in Spain: A qualitative study - Barceló-Soler, Alberto; García-Campayo, Javier; Araya, Ricardo; Doukani, Asmae; Gili, Margalida; García-Palacios, Azucena; Mayoral, Fermín; Montero-Marin, Jesus (Frontiers in Psychology, 2023)
Introduction Psychotherapies delivered via the Internet have been promoted as an alternative for improving access to psychological treatments. A conceptual working alliance model of blended (i.e., traditional face-to-face consultation combined with Internet-delivered psychotherapy) cognitive-behavioral therapy (b-CBT) for depression has been developed in the UK. However, little is known about how this important therapeutic process, namely the working alliance (WA), is developed and maintained in Internet-delivered cognitive-behavioral therapy without face-to-face consultation (i-CBT). The aim of this study was to evaluate the validity of the WA model of b-CBT in Spanish patients with depression receiving i-CBT. Methods Forty-one patients suffering from mild-moderate depression were interviewed to assess their experiences of an i-CBT program. Interviews were conducted with participants who received a self-guided application (n = 9), and low-intensity support (n = 10). Three group interviews were also conducted with patients who either did not start the program (n = 8) or did not complete it (n = 6), and with patients who did complete it (n = 8). Results Qualitative thematic content analysis was performed using the constant comparative method, which revealed four main themes: “bond,” “goals,” “task,” and “usability heuristics,” all consistent with the existing literature. However, a new subcategory emerged, called “anonymity,” which may highlight the social stigma that mental illness still has in the Spanish context. Conclusion Results suggest that the development and maintenance of the WA through i-CBT could offer a better experience of the therapeutic process and improve the clinical impact. Clinical Trial Registration Clinicaltrials.gov, identifier: NCT01611818.